Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense—18. Six Mexican and Central American species related to Odontocheila mexicana Laporte de Castelnau and O. ignita Chaudoir, with a description of O. potosiana sp. nov. (Coleoptera: Cicindelidae) - Moravec, Jiří; Brzoska, David; Huber, Ronald (Zootaxa, 2017)
Results of taxonomic revision of Mexican and Central American species of the genus Odontocheila Laporte de Castelnau, 1834, related to Odontocheila mexicana Laporte de Castelnau, 1834 (rectified publication date) and O. ignita Chaudoir, 1860 are presented. Redescriptions of O. mexicana, O. iodopleura Bates, 1872 and O. exilis Bates, 1884 are provided with their lectotype designations, and redescriptions of O. tawahka Johnson, 1996 and O. ignita are presented. O. exilis is restored to its original species status. Lectotype designations of O. cinctula Bates, 1881 and O. quadrina (based on Cicindela quadrina Chevrolat, 1835) are provided. The synonymy of O. cinctula with O. ignita is confirmed, as well as the synonymy of O. quadrina with O. mexicana. O. potosiana sp. nov. is described from Mexico as new for science; it represents the northernmost occurrence of the genus. A key to these related species is presented and their biology and distribution is treated. Illustrations in colour photographs of the habitus, diagnostic characters and variability are provided.